2007
DOI: 10.1159/000106468
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Selves: Temporality and Identity in Borderline Personality Disorder

Abstract: The concept of narrative identity implies a continuity of the personal past, present and future. This concept is essentially based on the capacity of persons to integrate contradictory aspects and tendencies into a coherent, overarching sense and view of themselves. In ‘mature’ neurotic disorders, this is only possible at the price of repression of important wishes and possibilities for personal development. Patients with borderline personality disorder lack the capacity to establish a coherent self-concept. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
130
0
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(153 citation statements)
references
References 42 publications
7
130
0
16
Order By: Relevance
“…Fuchs (2007) conceptualised BPD as a disorder of intersubjectivity with a fragmented self-narrative manifested in the typical clinical features of affect dysregulation, impulsivity, splitting of object relations, unstable relationships and chronic emptiness. According to Fonagy (2000), early experiences of lack of empathy or maltreatment by attachment figures impair the child's reflective capacities and sense of self when attachment representations are being formed.…”
mentioning
confidence: 99%
“…Fuchs (2007) conceptualised BPD as a disorder of intersubjectivity with a fragmented self-narrative manifested in the typical clinical features of affect dysregulation, impulsivity, splitting of object relations, unstable relationships and chronic emptiness. According to Fonagy (2000), early experiences of lack of empathy or maltreatment by attachment figures impair the child's reflective capacities and sense of self when attachment representations are being formed.…”
mentioning
confidence: 99%
“…In this context, Kernberg also proposed a concept of the splitting of representations to characterize borderline patients in whom the self and others are viewed at a given time as either all good or all bad without anything between this good-bad dichotomy (Westen, 1991). This splitting leads to disability to integrate positive and negative aspects of the self and others into coherent perceptions and produces "contradictory view" that things or persons are black or white, good or bad etc., and something between these polarities seems to be impossible (Kernberg, 1975;Fuchs, 2007). These contradictory representations of the self create disturbances of the mind.…”
Section: Psychoanalytic View Of Splitting and Dissociationmentioning
confidence: 99%
“…These contradictory representations of the self create disturbances of the mind. This splitting is based on a lack of higher-level of self-observational processes by which a person normally monitors ongoing thoughts for coherence and accuracy (Kernberg, 1975, Fuchs, 2007. As a consequence of some concepts and findings proposed by Kernberg, the defense mechanism of splitting has attained a special importance through conceptualization of borderline personality organization that had a significant influence on psychoanalytic understanding of splitting phenomena (Kernberg, 1975;Marmar & Horowitz, 1986).…”
Section: Psychoanalytic View Of Splitting and Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an ambulatorymonitoring technique, for example, Ebner-Priemer et al (2006) found that adults with BPD had a negative recall bias: they underestimated retrospective positive emotions and overestimated retrospective negative emotions. Given that an important feature of BPD is the unstable, fluctuating, volatile nature of the self-concept (Bender & Skodol, 2007;Fuchs, 2007), a more momentary, present-state measure of self-concept may have greater reliability and validity than a global one.…”
mentioning
confidence: 99%